Improvement of strains and production technologies for paddy straw mashrooms(volvariella spp.) - Pramod R (Department of Plant Pathology, College of Agriculture, 2004)
Paddy straw mushroom (Volvariella spp.) stands third among the commercially cultivated mushrooms in India. Even then its production is very low, compared to the other mushrooms. ICAR has given very much importance in the research on this mushroom under the All India Co-ordinated Mushroom Improvement Project (AICMIP) because of its high nutritive and medicinal values. As a step in improving the biological efficiency of this mushroom a work was conducted in the Department of Plant Pathology, College Agriculture, Vellayani during the period 2000-2003. We could achieve some positive results which will pave way for further improvement and refinement of the techniques.